What Do Teachers Know About Digital Safety?. Issue 3 (3rd July 2019) - Tomczyk, Łukasz
Abstract: The research objective was to determine the level of digital literacy (DL) among teachers. The scope of DL was narrowed to the issue of the safe use of electronic media. The research was conducted using a competency test and diagnostic survey. The following aspects of DL were measured: awareness of the mechanisms of communication with other Internet users and any threats resulting thereof, understanding what sexting is and what is meant by invasion of privacy, knowledge about copyright, ability to verify the credibility of information available online (the least developed area of DL), awareness of cyberbullying and the prevention thereof (the most developed DL skill), and the security of online financial operations. The study was conducted in the second half of 2016 in Poland and was commissioned by the Ministry of National Education responsible for the Bezpieczna+ (Safe+) project. The survey was carried out among 421 lower-secondary school teachers (covering three grades for children aged 12/13 to 15/16) from all over the country. The research results can be generalized at α = 0.95 level. The teachers surveyed showed different levels of DL. The teachers of technical subjects (including ICT) obtained the best results, whereas natural science teachers scored the lowest. Age was not a determinant of ICT expertise. A low level of DL and safety skills prevailed in the group of teachers who recently began their career in education (trainees). The group of beginner teachers in particular should be given educational support. This research also breaks the stereotype that young teachers have much more advanced DL than older teachers.